From Clones to Buds and Branches: The Use of Lung Organoids to Model Branching Morphogenesis Ex Vivo - Vazquez-Armendariz, Ana Ivonne; Herold, Susanne (Frontiers in Cell and Developmental Biology, 2021)
Three-dimensional (3D) organoid culture systems have rapidly emerged as powerful tools to study organ development and disease. The lung is a complex and highly specialized organ that comprises more than forty cell types that offer several region-specific roles. During organogenesis, the lung goes through sequential and morphologically distinctive stages to assume its mature form, both structurally and functionally. As branching takes place, multipotent epithelial progenitors at the distal tips of the growing/bifurcating epithelial tubes progressively become lineage-restricted, giving rise to more differentiated and specialized cell types. Although many cellular and molecular mechanisms leading to branching morphogenesis have been explored, deeper understanding of biological processes governing cell-fate decisions and lung patterning is still needed. Given that these distinct processes cannot be easily analyzed in vivo, 3D culture systems have become a valuable platform to study organogenesis in vitro. This minireview focuses on the current lung organoid systems that recapitulate developmental events occurring before and during branching morphogenesis. In addition, we also discuss their limitations and future directions.